Distinct germination responses may contribute to the distribution pattern of two Moquiniastrum species in different phytophysiognomies from the Brazilian savanna - Ferreira Ribeiro, Jonathan Wesley [UNESP]; Kolb, Rosana Marta [UNESP] (Elsevier B.V., 2016)
Understanding how germination traits can influence the distribution pattern of adult plants is still an important issue for seed ecologists and biologists. Here, we evaluated if seed germination responses to abiotic factors may be related to the occurrence of two Moquiniastrum species in different phytophysiognomies from the Brazilian savanna. To evaluate if germination responses are distinct between species, seeds of M. barrosoae (common to typical savanna) and M. polymorphum (common to typical and forested savanna) were set to germinate under different constant (5 to 40 degrees C) and alternating (15-30, 20-30, 25-30 and 25-35 degrees C) temperature regimes in light and dark conditions, different red:far-red ratios (0.1, 0.5, 2.0 and 7.2 R:FR) of light, and water availability (0 to-1.0 MPa) in controlled experiments. Seed germination responses were distinct between species, with M. polymorphum presenting higher germinability over a wider temperature range, with lower light requirement for germination, less sensitivity to alteration of R:FR ratios and higher tolerance to water limitation compared to M. barrosoae, which presented more specific environmental requirements to seed germination. Therefore, we demonstrate that seed germination responses may contribute to the distribution pattern observed in adult plants, since the more widely distributed species (M. polymorphum) presented higher germinability over a broader range of environmental conditions, which may enable this species to occur in different phytophysiognomies compared to the species with the more restricted distribution area (M. barrosoae). (C) 2016 Elsevier GmbH. All rights reserved.
Keywords: Seeds; Cerrado; Asteraceae; Temperature range; Light requirement; Water limitation